PEMBERIAN LAYANAN PROSTHESIS DAN PENDAMPINGAN DIRI PASIEN PASCA AMPUTASI TRANSTIBIAL SETELAH MENDAPATKAN PROSTHESIS BAGI MASYARAKAT DENGAN EKONOMI KURANG MAMPU - Syaifuddin, Muhammad; Ningsih, Cica Trimandasari (Poltekkes Kemenkes Malang, 2025)
Amputation is the act of separating part or all of an extremity of the body as a last option if the organ problem cannot be repaired by other methods or can pose a risk of infection. Post-amputation often results in feelings of loss, and lack of self-confidence, and hinders daily activities. A prosthesis is a solution to replace missing body parts, allowing amputees to be independent and not dependent on other people. However, cost is an obstacle for economically disadvantaged people to be able to have a prosthesis. This research aims to provide prosthesis services and assistance for post-amputation people with economic limitations. This research method uses qualitative research with a case study research type. Data were collected using analytical interviews and observations on respondents who had experienced transtibial amputation aged 45 years. The results demonstrate respondents' understanding of the importance of social support and prosthesis accessibility. Motivation and quality of life increase, so that respondents can carry out their daily activities better and more independently.